Coastal Vulnerability Assessment for Community Resilience on Abrasion: Case of Bugel Coast, Kulon Progo Regency, Indonesia - Cahyadi Ramadhan; Dina Ruslanjari; Diana Puspitasari; Gading Dita Indasari; Naufal Sandro (Universitas Gadjah Mada, 2022)
The coastal boundary can be optimized for settlement and agriculture site based on a spatial plan for Kulon Progo Regency 2012–2032 within a minimum distance of 100m from the coastline. The location of ring 1 local transmigration settlement on the Bugel Coast is less than 100 m. The increasing trend in coastal erosion caused by climate change is a major contributing factor to the reduction of coastal borders. Thus, rapid assessment of coastal erosion vulnerability is necessary to determine an effective coastal management response. This paper aims to analyze the coastal erosion level using vulnerability assessment, geomorphology of coastal areas, and community resilience impact. The methods used in the mapping of coastal segments are smartline and coastal vulnerability index (CVI). The Smartline method is depicted with a line that runs along the coast with information on geomorphological conditions, whereas the CVI method will give weight to each physical parameter of coastal erosion vulnerability. Results showed that the average area of Bugel Coast decreased by 4,794.94 m2 /year and retreated by 4.36 m/year until the borders become closer to one another, thereby threatening the settlement area. The coastal erosion vulnerability was dominated by a moderate level of 325.14 m (30.48%) to a high level of 322.31 m (30.22%) of the total study areas. This result indicated the huge risk of coastal erosion. Therefore, effective community adaptation and mitigation strategies should be considered to reduce the degradation of coastal border resources and ensure the sustainability of local life, such as the combination of structural and non-structural mitigations that prioritize the sustainability of coastal ecosystems.